2010
DOI: 10.1371/journal.pcbi.1000808
|View full text |Cite
|
Sign up to set email alerts
|

The Organization of Local and Distant Functional Connectivity in the Human Brain

Abstract: Information processing in the human brain arises from both interactions between adjacent areas and from distant projections that form distributed brain systems. Here we map interactions across different spatial scales by estimating the degree of intrinsic functional connectivity for the local (≤14 mm) neighborhood directly surrounding brain regions as contrasted with distant (>14 mm) interactions. The balance between local and distant functional interactions measured at rest forms a map that separates sensorim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

41
402
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 386 publications
(443 citation statements)
references
References 78 publications
41
402
0
Order By: Relevance
“…Stronger FCS-rCBF correlation was found in long-range connectivity in the current study, suggesting that brain hubs with abundant long-range connections couple more closely with blood/energy supply to facilitate their greater participation in neural processes (16). High short-range connectivity was observed in mPFC, lPFC, and primary sensorimotor and visual cortices, which corresponds well with a previous study (18). However, the spatial distribution of short-range hubs showed a relative lower correlation with the rCBF map, probably due to the mismatch between short-range FCS and rCBF in the primary sensory and motor areas.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Stronger FCS-rCBF correlation was found in long-range connectivity in the current study, suggesting that brain hubs with abundant long-range connections couple more closely with blood/energy supply to facilitate their greater participation in neural processes (16). High short-range connectivity was observed in mPFC, lPFC, and primary sensorimotor and visual cortices, which corresponds well with a previous study (18). However, the spatial distribution of short-range hubs showed a relative lower correlation with the rCBF map, probably due to the mismatch between short-range FCS and rCBF in the primary sensory and motor areas.…”
Section: Discussionsupporting
confidence: 91%
“…Disparate spatial patterns of the number of short-versus long-range functional connections have been reported previously (18), suggesting disproportionate metabolic demands of the two measures. In the present study, brain regions with high long-range FCS were mainly located in association cortical areas including mPFC/lPFC, paralimbic regions of PCC/PCu, and temporal and parietal cortices, showing a high spatial overlap with the rCBF map.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…While in this work geodesic mapping was not performed, node degree of short-and long-range connectivity is significantly coupled across cortical regions; this incidentally also allays concerns over the impact of short-range correlation introduced by spatial Gaussian smoothing of the time-series. 87 Second, only one spatiotemporal window (the one accessible to functional MRI) was considered, and it is necessary to determine whether the observed relationship also holds at finer temporal resolution (1 ms vs. 1 s scale) and on the microscopic and mesoscopic levels. This will help clarify if the observed relationships are generalizable rather than "epiphenomena" of specific experimental settings.…”
Section: Analogy Between Brain and Single-transistor Chaotic Oscilmentioning
confidence: 99%
“…For example, some studies have reported consistent components with potential functional relevance, consisting of regions known to be involved in motor, visual, and auditory processing, memory, executive functioning, and the so-called default-mode network [49] . In addition, some studies have explored the spatially-distributed patterns of connectivity, such as regional homogeneity [50] and the degree/density of local and distant connectivity [51,52] . including scale scores [53,54] , illness duration [44,55] and genotypic variations [35,56] .…”
Section: A Brain Network Consists Of Two Basic Componentsmentioning
confidence: 99%